산업안전보건 규제완화에 대한 보건관리자의 인지도 및 보건관리자의 평가 - 박수만(Soo Man Park); 정혜선(Hye Sun Jung); 이복임(Bok Im Lee) (지역사회간호학회지, 2003)
The purpose of this study is to analysis the awareness and opinion of occupational health managers on the deregulation of occupational safety and health. The data were collected by using constructed questionnaires from December 1 to December 20, 2000. The subjects for this study were 107 respondents. The results were as follows ; 1. The highest awareness score was voluntary employment for occupational health doctor. High awareness score was exemption from obligatory education for occupational health manager, and expansion cover range of group occupational health agencies. 2. Most of the occupational health managers had a negative opinion on the deregulation of occupational safety and health. In particular, one of the most negative opinions was no restrictions on occupational health managers holding other jobs. 3. The correlation between awareness and opinion on the deregulation of occupational safety and health was negative, showing that the negative opinion on the deregulation of occupational safety and health tended to increases as awareness increases.